2018
DOI: 10.5455/njppp.2018.8.0830324082017
|View full text |Cite
|
Sign up to set email alerts
|

Association of ABO and Rh blood groups with type 2 diabetes mellitus in Muzaffarnagar city

Abstract: Background:The "ABO" blood group system is associated with some diseases including gastric and duodenal ulcer, hepatitis B1, vascular diseases, abdominal aortic aneurism, and cancers. Some epidemiological studies demonstrated the linkage among the "ABO" blood group and the risk of type 2 diabetes mellitus (DM). Aims and Objective -This study aimed to find out the possible linkage between "ABO" and "Rhesus" blood groups with type 2 DM. Material and Methods: This study was carried out in Department of Physiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 15 publications
(18 reference statements)
4
23
3
Order By: Relevance
“…The result of the present study showed that the Rh factor was not associated with T2DM. Similar results were reported by studies in India [ 37 ] and Algeria [ 26 ]. However, a study conducted in Pakistan [ 5 ] indicated that Rh-negative blood groups and T2DM had a significant association.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The result of the present study showed that the Rh factor was not associated with T2DM. Similar results were reported by studies in India [ 37 ] and Algeria [ 26 ]. However, a study conducted in Pakistan [ 5 ] indicated that Rh-negative blood groups and T2DM had a significant association.…”
Section: Discussionsupporting
confidence: 91%
“…The reason for this protective effect of the O blood group might be the low level of inflammatory mediators like factor VIII-VWF complex, intercellular adhesion molecule-1 (ICAM-1), and TNF-2 [ 31 , 32 ]. Inconsistent to the current result, a study in India [ 37 ] reported that blood group O had increased risk of developing DM as compared to other blood groups. The reasons for the observed difference might be the geographical, environmental, and genetic differences in which these studies were conducted.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…According to the results of this study, there was no statistically significant relationship between the variable of Rh and diabetes. This was consistent with the study of Aggarwal et al [18], but in their study, Rh + in the case group (diabetic patients) was higher than Rh + in the control group (healthy participants). Other studies also showed the same results [21,25].…”
Section: Discussion/conclusionsupporting
confidence: 93%
“…Some studies have been conducted on the association between blood type and diabetes. They concluded that diabetes can be related to blood group B [15,16], blood group A [17] and blood groups O and AB [18]. Also several other studies have explored the relationship between ABO blood group and diabetes, but their findings were mostly inconsistent [19][20][21].…”
Section: Introductionmentioning
confidence: 99%